EFEKTIVITAS ZAKAT PRODUKTIF MELALUI MUSTAHIK INCOME GENERATING PROGRAM (MIGP) PADA YAYASAN BAITUL MAL (YBM) BRILiaN BANDA ACEH - Munawarah (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2022)
Productive zakat is believed to be able to improve the standard of living of mustahik to be more economically empowered in accordance with the objectives of productive zakat distribution in the law. In this case, the Baitul Mal Foundation (YBM) BRILiaN Banda Aceh applies it through the Mustahik Income Generating Program (MIGP) in agriculture. The problem in this study is the standard of YBM BRILiaN's assessment of the level of success and independence of mustahik in the implementation of the MIGP program, the level of transparency and accountability of YBM BRILiaN in the distribution of productive zakat through the MIGP program, and the review of Law Number 23 of 2011 on the effectiveness of productive zakat distribution at YBM BRILiaN. The research method uses a qualitative method in the form of descriptive analysis with an empirical normative approach. Data collection through interviews and documentation. The results showed that the research standards for assessing the level of success and independence of Mustahik were, namely: first, Mustahik can eliminate harm to himself and his responsibility; second, Mustahik is able to empower himself without help from others; and third, Mustahik gets a change in status from Mustahik to Muzakki. The distribution of zakat funds has been carried out very transparently, starting from the determination of mustahik to the method of distribution, and in terms of responsibility, YBM BRILiaN ensures that there is assistance for mustahik and there are reports on the development of mustahik businesses. As for the perspective of Law No. 23 of 2011 on the MIGP program, the results show that this program is effective in improving the quality of the mustahik economy in accordance with the objectives of productive distribution of zakat funds, and its realization has been carried out by considering the provisions in the Zakat Management Law.